2012
DOI: 10.3758/s13414-011-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Music training enhances the rapid plasticity of P3a/P3b event-related brain potentials for unattended and attended target sounds

Abstract: Neurocognitive studies have shown that extensive musical training enhances P3a and P3b event-related potentials for infrequent target sounds, which reflects stronger attention switching and stimulus evaluation in musicians than in nonmusicians. However, it is unknown whether the short-term plasticity of P3a and P3b responses is also enhanced in musicians. We compared the short-term plasticity of P3a and P3b responses to infrequent target sounds in musicians and nonmusicians during auditory perceptual learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
4
32
0
Order By: Relevance
“…Active tasks were adaptive, that is, the better participant could discriminate the more difficult deviants. In a previous study, we found that musicians discriminated deviating sounds in active tasks better than non-musicians (Seppänen et al, 2012). There was, however, no significant difference in the number of standard or deviant trials in Active task 1, which was used as a probe for the active attention.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Active tasks were adaptive, that is, the better participant could discriminate the more difficult deviants. In a previous study, we found that musicians discriminated deviating sounds in active tasks better than non-musicians (Seppänen et al, 2012). There was, however, no significant difference in the number of standard or deviant trials in Active task 1, which was used as a probe for the active attention.…”
Section: Discussionmentioning
confidence: 71%
“…There was, however, no significant difference in the number of standard or deviant trials in Active task 1, which was used as a probe for the active attention. Furthermore, only non-musicians demonstrated an improvement in the behavioral discrimination of difficult deviations, whereas in musicians, the discrimination remained at the maximum level (Seppänen et al, 2012). Based on these arguments, it is unlikely that the present finding of the standard sound enhancement in musicians would be caused by the more frequent exposure to deviating sounds during the active task.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the amplitude of these responses was correlated with the age at which musicians began their musical training. Several electroencephalographic studies have also revealed an increase of the amplitude of event-related potential (ERP) components (N100, P200, MMN, P300 among others) in musicians (Trainor et al, 1999;Shahin et al, 2003Shahin et al, , 2007Jongsma et al, 2004;Magne et al, 2006;Musacchia et al, 2007;Seppa¨nen et al, 2012;Habibi et al, 2013;Kaganovich et al, 2013;Ungan et al, 2013;Virtala et al, 2014). For example, Shahin et al (2003) found that highly skilled violinists and pianists exhibited larger N1 and P2 responses compared with non-musicians when they passively listened to musical tones (violin, piano) and pure tones matched in fundamental frequency to the musical tones.…”
Section: Introductionmentioning
confidence: 94%
“…While the role of attention with respect to musicians' perception remains debated (e.g., Baumann et al, 2008;Koelsch et al, 1999), research has shown that musicians differ from nonmusicians in the way that attention modulates electrophysiological indices of auditory perception (e.g., Tervaniemi et al, 2005Tervaniemi et al, , 2009Seppänen et al, 2012; see also Marie et al, 2011). Compared to non-musicians, musicians show increased N2b component amplitudes for attended intensity, frequency and duration deviances in speech and musical sounds (Tervaniemi et al, 2009), and significant reductions in P3b amplitudes when attending to subtle pitch deviances .…”
Section: Musicianship Attention and Cognitionmentioning
confidence: 99%